IMPLEMENTATION OF GOOD GOVERNANCE PERSPECTIVE IN IMPROVING THE QUALITY OF PASSPORT ISSUANCE SERVICES AT THE CLASS I TPI PONTIANAK IMMIGRATION OFFICE - Agus Dwi Riyanto; Rusdiono; S.Y. Pudjianto (RADJA PUBLIKA, 2025)
This thesis discusses the quality of public immigration services in passport issuance from the perspective of good governance at the Class 1 TPI Immigration Office in Pontianak City. This research is based on the phenomenon of low integrity in immigration services, particularly in passport issuance. Public services are part of national development to increase community participation. In relation to this, the Class I TPI Immigration Office in Pontianak provides public services aimed at improving quality and enhancing the services provided by the Class I TPI Immigration Office in Pontianak (in accordance with the perspective of good governance). To determine the level of success in the implementation of public service quality at the Class I TPI Immigration Office in Pontianak, the author conducted field research. To ensure the validity of the data, the researcher employed several methods in the study, including observation, interviews, and documentation. Based on the findings of the research, it can be concluded that the quality of public services provided by the Class I TPI Immigration Office in Pontianak is already in line with the Good Governance perspective.